Field experiment of lignosulfonate preflushing for surfactant adsorption reduction - 홍성안; J. H. Bae (1990)
Lignosulfonate was field tested as a sacrificial absorbate in conjunction with the ongoing Glenn Pool surfactant flood expansion project. A 2 wt% lignosulfonate solution was injected for 10 days as part of the preflush in this project. Results of the analyses of two observation well samples were interpreted for the effect of lignosulfonate on sulfonate adsorption and process performance. Even though the evidence was ambiguous, we concluded that the low-cost lignosulfonate preflushing was beneficial to surfactant flooding.